The Effect of Dopaminergic Medication on Joint Kinematics during Haptic Movements in Individuals with Parkinson’s Disease - Kuan-yi Li; Pei-yi Chu; Kristen A. Pickett (Behavioural Neurology)
This study examined whether altered joint angular motion during haptic exploration could account for a decline in haptic sensitivity in individuals with PD by analyzing joint position data during haptic exploration of a curved contour. Each participant’s hand was passively moved by a robotic arm along the edges of a virtual box (5 cm × 15 cm) with a curved left wall. After each trial, participants indicated whether the contour was curved or straight. Visual, auditory, and tactile cues were occluded, and an electrogoniometer recorded shoulder and elbow joint angles during each trial. The PD group in the OFF state had a higher mean detection threshold (4.67 m−1) than the control group (3.06 m−1). Individuals with PD in the OFF state also had a significantly greater magnitude of shoulder abduction than those in the ON state (p=0.003) and a smaller magnitude of elbow flexion than those in the ON state or compared to the control group (both p<0.001). These findings suggest that individuals with PD employ joint configurations that may contribute to haptic insensitivity. Dopamine replacement therapy improved joint configurations during haptic exploration in patients with PD, suggesting a role for dopaminergic dysfunction in PD-related haptic insensitivity.